2010
DOI: 10.1002/adsc.201000499
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Synthesis and Ring‐Opening Reactions of Monofluorinated Epoxides Derived from α‐Fluorosulfoximines

Abstract: Monofluorinated epoxides were successfully prepared through the O-cyclization reaction between a-fluorosulfoximines and ketones. The obtained fluoroepoxides were found to readily undergo an interesting ring-opening process (involving both a C À F bond cleavage and another C À F bond formation) in the presence of titanium tetrafluoride or pyridinium poly(hydrogen fluoride) to afford afluorinated ketones. The later process constitutes a formal catalytic 1,2-fluorine shift reaction.Keywords: epoxides; fluorine; f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
26
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 30 publications
1
26
0
Order By: Relevance
“…To our delight, when 1 b with an electron-donating TBS substituent was used, its reaction with 2 s proceeded smoothly to afford olefin 3 s in moderate yield with high E selectivity (entry 2). In the case of 1 c, the formation of the corresponding monofluoroepoxide was detected, [16] whereas in the case of 1 d, the product of addition to the carbonyl group was obtained as reported previously. Reactions with either N-tosyl or N-TBS-substituted S-phenylsulfoximine (substrates 1 c and 1 d) failed to produce the olefination product (Table 1, entries 3 and 4).…”
supporting
confidence: 79%
“…To our delight, when 1 b with an electron-donating TBS substituent was used, its reaction with 2 s proceeded smoothly to afford olefin 3 s in moderate yield with high E selectivity (entry 2). In the case of 1 c, the formation of the corresponding monofluoroepoxide was detected, [16] whereas in the case of 1 d, the product of addition to the carbonyl group was obtained as reported previously. Reactions with either N-tosyl or N-TBS-substituted S-phenylsulfoximine (substrates 1 c and 1 d) failed to produce the olefination product (Table 1, entries 3 and 4).…”
supporting
confidence: 79%
“…However, it has been reported that many simple fluoroepoxides are rather sensitive to moisture and can readily decompose during the purification, 8,10 and we also found that the stability of the fluoroepoxides derived from fluorosulfoximines and aryl ketones is closely linked with the electronic nature of the functionalities on aryl groups (Table 1). Although strongly electron-deficient fluoroepoxides can be easily purified by silica gel column chromatography, attempts to purify the tetrasubstituted electron-neutral fluoroepoxides with moderate stability by using silica gel column chromatography resulted in ring-opening products (a mixture of 1,2-fluorine migration product 5 and a considerable amount of defluorination products).…”
Section: Improved Preparation Of Fluoroepoxidesmentioning
confidence: 54%
“…8 Through this fluorine migration reaction, many structurally diverse α-fluorinated ketones can be efficiently constructed. 8 Through this fluorine migration reaction, many structurally diverse α-fluorinated ketones can be efficiently constructed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…2 Since 2008, N,N-dimethyl α-fluoromethyl sulfoximinium salts (by research groups led by Shibata 4,5 and Prakash 6 ), N-tosyl racemic α-fluoro sulfoximines (by Hu's group [7][8][9] ), and other α-fluoro sulfoximines (by Magnier's group 10 ) have been exploited for fluoroalkylation reactions. Inspired by recent developments in the synthesis of chiral fluorinated molecules, they envisioned several conceptually new chiral fluoroalkylation reagent controlled diastereoselective and enantioselective nucleophilic reactions by taking advantage of the stereogenic center of sulfur in sulfoxi m ines.…”
mentioning
confidence: 99%